Modification of the rice husk activated carbon using chemical method as solid adsorbent for CO2 capture - Abdullah, Hamidah; Khan, Maksudur Rahman; Jamari, Saidatul Shima (2019)
Carbon dioxide (CO2) is one of the greenhouse gases that contributes to global warming. Therefore, it is crucial to develop technologies to overcome the increasing of CO2 emission. One of the promising approach is CO2 capture by adsorption process using solid adsorbent such as activated carbon (AC). The AC is attracted much attention due to its high surface area properties. The high surface area is required for physical interactions with CO2 molecules. Besides, the chemical interactions between acidic CO2 and the adsorbent could be occurring if the adsorbent has basic site. Thus, this research has put a much effort to synthesis a new modified adsorbent that able to physically and chemically adsorb CO2 to boost the CO2 adsorption capacity. The commercial rice husk activate carbon has been used as adsorbent basis. Then, the chemically modification has been done by mixing the rice husk AC with polyethyleneimine (PEI), 3-triethoxysilylpropylamine (APTES) and ethylenediamine (EDA). The physicochemical properties of the synthesized adsorbents were then analyzed using Scanning Electron Microscopy (SEM), Fourier Transform Infra-red (FTIR) Spectroscopy, N2 physisorption analysis and Thermogravimetric analysis (TGA). Besides, the performance of the synthesized adsorbents in CO2 capture were also investigated. In general, it was observed that the CO2 adsorption capacity using modified-AC was enhanced compared to AC depending on the chemical used due to the change of physical and chemical properties. It can be concluded that the AC containing basic site have been successfully synthesized and the increase of CO2 adsorption capacity using modified-AC was due to the additional basic site on the AC. The findings from this research are expected can be contribute to the development of the existing CO2 capture technology.